The Impact of Covid-19 on Gold Price in Indonesia Using ARIMA Intervention - Dyah Makutaning Dewi; Alvian Ferrandy; Muhammad Zaky Nafi'; Nasrudin (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
On March 2, 2020, Indonesia experienced first case of Covid 19. As a result, investors should be careful in investing so that investors choose gold in investing. Purpose of this study is analyze impact of Covid-19 on gold price in Indonesia. Research method uses ARIMA intervention. The results showed that the impact of Covid-19 on gold price in Indonesia is gradual temporary, meaning the intervention to influence the movement of gold price gradually and temporarily. Intervention of Covid-19 cases against gold price in Indonesia began to be felt after two weeks of the first case of Covid-19 in Indonesia which demonstrated by the increase in the gold price out of ordinary since the 16th day. On the 19th day after intervention, the gold price in Indonesia decreased. Furthermore, the gold price in Indonesia is again rising and expected to increase. The forecast results of the next 31 days show gold price in Indonesia has always increased. When Covid-19 has not been able to be resolved so that the confirmed positive case of Covid-19 continues to increase, gold investment is one of the safe investments. However, investors should pay attention to gold price movements if they want to invest in gold. Keywords: ARIMA Intervention, Covid-19, Gold Price JEL Classification: E22, H54, O16